Antibacterial Potency of Black Garlic Extract from Allium sativum on Escherichia coli - Harun, Muhammad Alief; Buraena, Sultan; Wello, Eny Arlini; Idrus, Hasta Handayani; Arsal, Andi Sitti Fahirah (Fakultas Kedokteran Universitas Muslim Indonesia, 2021)
Background: Diarrhea is still one of the global issues especially in developing countries. Diarrhea can be caused by either an infectious agent or a non-infectious agent. Escherichia coli is one of the infectious agents that is responsible for causing diarrhea. Garlic (Allium sativum) is a plant that has a good antibacterial activity potential because of its organosulfur and phenolic compound. Black garlic is the product of spontaneous fermentation of garlic that has improved its bioactive compounds. Content: Antibacterial potency of black garlic extract on Escherichia coli is shown on the resistance zone that formed where the lowest zone diameter is 9,67 mm while the highest zone is 24 mm. The fermentation of black garlic happened at the temperature of 70-80Â°C with 75-80% for 28-40 days. Conclusion: Black garlic is shown to exhibit antibacterial activity against bacteria such as Escherichia coli. This fermented product has the potential to be a therapeutic agent for diseases caused by Escherichia coli.